Performance Analysis of Administrative Staff at the Faculty of Social and Political Sciences Universitas Negeri Yogyakarta Using the Customer Satisfaction Index and Importance Performance Analysis - Perdaning Widyanti; Aprilianti Wulandari; Triyanto; Alnico Imam Nugroho; Shahzeb (Faculty of Educational Sciences, Universitas Negeri Yogyakarta, 2026)
This study aims to analyse the performance of educational staff at Yogyakarta State University (UNY) using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods. Data was collected through questionnaires from 391 student respondents from various study programmes. The CSI calculation results showed a satisfaction level of 75.46%, which falls into the satisfied category. The IPA analysis identified service indicators that need to be prioritised for improvement, particularly in terms of supporting facilities and access to library collections. Overall, the performance of educational staff is considered good but still requires improvement in certain aspects to align with student expectations.